The Influence of Service Quality and Timeliness on Passenger Loyalty, Yogyakarta International Airport Train - Nanda Ahda Imron; Dian Febryliana; Arinda Leliana; Adya Aghastya; Riz Rifai Oktavianus Sasue; Arif Devi Dwipayana (Jurnal Teknologi Transportasi dan Logistik, 2023)
Yogyakarta International Airport (YIA) is a new airport located in Kulon Progo Regency, Yogyakarta. One of the transportation modes that can be used to reach the airport is the YIA Airport Train. With the increasing number and routes of airlines operating at YIA, the number of airport train passengers has also increased. However, this increase in passenger numbers has not been accompanied by an improvement in the quality of service provided and train delays are still occurring. This study aims to determine the influence of service quality on passenger loyalty, on-time performance on passenger loyalty, and the combined influence of service quality and on-time performance on passenger loyalty. The methods used in this study are Structural Equation Modeling (SEM) and multiple linear regression analysis. Data processing was done using SmartPLS 3.2.9 software for the SEM method and IBM SPSS 20 for the multiple linear regression analysis method. The results of this study indicate that both methods used support each other's findings. The results show that service quality has an impact on passenger loyalty. On-time performance also has an impact on passenger loyalty. Additionally, service quality and on-time performance have a positive and significant influence on passenger loyalty. In conclusion, it can be inferred that the better the service quality and on-time performance provided by the service provider, the higher the passenger loyalty will be.